2008
DOI: 10.4278/ajhp.22.5.336
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Mediated Intervention Tailored on Transtheoretical Model Stages and Processes of Change Increases Fruit and Vegetable Consumption among Urban African-American Adolescents

Abstract: Purpose-To examine the efficacy of an intervention based on the transtheoretical model (TTM) for increasing fruit and vegetable consumption among economically disadvantaged AfricanAmerican adolescents. Design-Pretest-posttest quasi-experimental study.Setting-Youth services agencies located in New York, New Jersey, and Pennsylvania. Agencies were assigned to computer intervention (CIN) and nonintervention control study arms.Subjects-A total of 507 African-American adolescents ages 11 to 14 years.Intervention-Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(134 citation statements)
references
References 22 publications
1
129
0
4
Order By: Relevance
“…In the present study, there was a significant increase in fruit and vegetable consumption with progress in the stages of change. This finding is in agreement with previous studies that found higher level of fruit and vegetable consumption with a progress in stages of change (21)(22)(23)). In the study by Bawadi et al (26) among university staff, those at the pre-contemplation stage consumed a significantly lower amount of fruits and vegetables (24).…”
Section: Resultssupporting
confidence: 83%
“…In the present study, there was a significant increase in fruit and vegetable consumption with progress in the stages of change. This finding is in agreement with previous studies that found higher level of fruit and vegetable consumption with a progress in stages of change (21)(22)(23)). In the study by Bawadi et al (26) among university staff, those at the pre-contemplation stage consumed a significantly lower amount of fruits and vegetables (24).…”
Section: Resultssupporting
confidence: 83%
“…Despite evidence in the TTM literature showing a situation of some confusion and entrenched disputes, interventions based on health promotion/TTM constructs are reported to be effective in PA and healthy eating promotion (41)(42)(43)(44)(45)(46) .…”
Section: Discussionmentioning
confidence: 99%
“…21 Patients received tailored counseling for each target behavior based on their current stage of change. SMI used the processes of change using the cognitive and behavioral activities found to be most effective for each stage, 22,23 and incorporated decisional balance and self-efficacy. For the decisional balance, the pros and cons of each behavior were elicited, and the counselor explored why each pro endorsed was important to the participant.…”
Section: Interventionmentioning
confidence: 99%